Transformasi Energi dan Ekonomi: Dampak Investasi Energi Terhadap Konsumsi Listrik dan Ketimpangan Ekonomi di Indonesia - Darwin, Ranti; Hidayat, Muhammad; Widiarsih, Dwi; Hadi, M.Fikry; Asnawi, Mizan (Akuntansi & Ekonomika, 2025)
This study aims to explore the influence and simultaneous relationship between electricity consumption and economic inequality in Indonesia. This study uses time series data for the country of Indonesia for the period 2000-2023 sourced from the BPS. This research method uses simultaneous equations with the 2SLS (Two-Stage Least Square) approach as its best method with more consistent results and lower standard errors compared to the 3SLS model. The results of this study indicate that in the first stage of estimation, economic inequality and energy investment have a negative effect on electricity consumption in Indonesia. Electrification has a positive effect on electricity consumption in Indonesia. However, household electricity sales do not affect electricity consumption in Indonesia. In the second stage of estimation, electricity consumption and unemployment rates have a negative effect on economic inequality in Indonesia. Furthermore, economic growth has a positive effect on economic inequality in Indonesia.